Entrepreneurship Education and Multicultural Values in Nigeria: A Strategy for Job Creation and Unemployment Reduction - Aroyehun Hafsat Odunola; Hussain A. B. Sani (Solo Universal Journal of Islamic Education and Multiculturalism, 2025)
Objective: This study aims to explore the role of entrepreneurship education in addressing unemployment and job creation in Nigeria, focusing on its potential to enhance self-employment, employability, and economic growth. Theoretical framework: The framework integrates entrepreneurship education with multicultural values such as tolerance, inclusivity, and diversity, emphasizing their role in shaping adaptable, socially responsible entrepreneurs. Literature review: Previous studies highlight entrepreneurship education’s ability to reduce unemployment and foster self-sufficiency. Additionally, the integration of multicultural values is seen as essential for fostering globally adaptive and socially responsible entrepreneurship. Method: The study uses a qualitative approach, reviewing literature and policies to analyze the benefits and challenges of entrepreneurship education in Nigeria, particularly regarding unemployment and cultural diversity. Results: The findings show that entrepreneurship education, enriched with multicultural values, can mitigate unemployment, drive economic growth, and foster innovation. It highlights the importance of creating a supportive economic environment for entrepreneurship. Implications: The study suggests that integrating entrepreneurship education with multicultural values can generate new economic opportunities and reduce unemployment, urging policymakers to create an enabling environment for entrepreneurship. Novelty: This study introduces the novel idea of combining multicultural values with entrepreneurship education, proposing that this integration is key to developing responsible entrepreneurs capable of succeeding in diverse global markets.